The Concept of Moral Education for University Students: A Study of al-Buzaidi’s Book al-Adab al-Mardhiyyah - Zainal Abidin, Muhammad Hosnee; Surtahman, Asma' Wardah; P. Rameli, Mohd Faizal; Johari, Muhd Khudri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
Moral excellence (akhlak) holds paramount significance in Islam, serving as the criterion for a Muslim’s standing before Allah. The Prophet Muhammad (PBUH) emphasized the importance of benevolence and deeds over outward appearances, highlighting the inseparable connection between ethical conduct and spiritual integrity. Despite this high regard for moral virtues, embodying them remains a significant challenge for Muslim youth, particularly among university students. The era of globalization, coupled with the pervasive influence of social media and mass media, often exerts a detrimental impact on adolescents, contributing to a pressing concern over behavioral misconduct issues within higher education institutions. This study examines the concept of moral education for university students by analyzing Al-Buzaidi’s book, Al-Adab Al-Mardhiyyah. This research aims to provide an in-depth understanding of the principles of moral excellence as a guide for contemporary challenges faced by young Muslims in a university setting.